2019
DOI: 10.1016/j.nmni.2019.100572
|View full text |Cite
|
Sign up to set email alerts
|

Flaviviruses as agents of childhood central nervous system infections in Brazil

Abstract: Flaviviruses are agents of a major emerging human public health issue and members of this genus have been associated with central nervous system (CNS) infections. In Brazil, a country endemic for some arboviruses, the most clinically relevant neurotropic flaviviruses include Dengue virus and Zika virus. Flaviviruses cause diseases ranging from mild or sub-clinical infections to severe cases as CNS infections. There is a lack of data about the incidence of flaviviruses in the CNS of children in Brazil. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Our observations may not conclusively demonstrate that ILHV infection led to the brain hemorrhage and death in a patient with an acute neurological syndrome and underlying conditions (diabetes and hypertension). Considering the increasing incidence of arboviruses with unusual manifestations ( [51][52][53] and reviewed in [54][55][56]), and their potential tropism for the invasion of the CNS, leading to long-term neurofunctional sequelae, this report highlights the need for vigilance among physicians, healthcare providers, and researchers alike for arbovirus infections in patients presenting with meningoencephalitis and cerebrovascular events. Furthermore, this study demonstrates the importance of comprehensive arbovirus surveillance beyond urban arboviruses (e.g., DENV, CHIKV, and ZIKV), suggesting that urban and peri-urban populations may be at risk for ILHV infection and other emerging zoonotic arboviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations may not conclusively demonstrate that ILHV infection led to the brain hemorrhage and death in a patient with an acute neurological syndrome and underlying conditions (diabetes and hypertension). Considering the increasing incidence of arboviruses with unusual manifestations ( [51][52][53] and reviewed in [54][55][56]), and their potential tropism for the invasion of the CNS, leading to long-term neurofunctional sequelae, this report highlights the need for vigilance among physicians, healthcare providers, and researchers alike for arbovirus infections in patients presenting with meningoencephalitis and cerebrovascular events. Furthermore, this study demonstrates the importance of comprehensive arbovirus surveillance beyond urban arboviruses (e.g., DENV, CHIKV, and ZIKV), suggesting that urban and peri-urban populations may be at risk for ILHV infection and other emerging zoonotic arboviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Although flaviviruses are not always neuro-invasive, they are able to infect neurons [ 61 , 62 ]. It has been shown that flavivirus neuropathogenesis is related to the apoptosis of infected neuronal cells and/or the immune response induced by the immune cells, because factors produced by microglia may be toxic to neurons [ 63 , 64 , 65 ].…”
Section: Viruses Commonly Associated With Cns Infection In Brazilmentioning
confidence: 99%
“…Dengue-related meningitis is rare, but it has been previously described in a few reports, including in children, for whom the acute onset of fever and symptoms such as headache, vomiting, and/or nuchal rigidity were described [ 28 , 65 , 73 , 81 , 82 , 83 ].…”
Section: Viruses Commonly Associated With Cns Infection In Brazilmentioning
confidence: 99%
“…The most important neurotrophic alphavirus is VEEV, which caused many outbreaks in South, Central, and North America [15]. CHIKV is now becoming a re-emerging epidemic with cases reported in more than 45 countries and has caused severe diseases with neurological complications affecting all age groups [15][16]. CHIKV is transmitted to humans through mosquito vectors where the vertebrate animals serve as the reservoirs in epizootic cycles, but in current epidemics, humans serve as the reservoirs.…”
Section: Epidemiologymentioning
confidence: 99%
“…Tick-borne flaviviruses have been considered medically important as they cause about 10,000 to 15,000 human cases every year in Europe and Asia [15]. Mosquito-borne flaviviruses are considered as the most important neurotropic flaviviruses [16].…”
Section: Epidemiologymentioning
confidence: 99%